Training profiles and motivation of male and female youth soccer players - Rumpf, M. C.; Schneider, A. S.; Schneider, C.; Mayer, H. M. (International Journal of Sports Science and Coaching, 2014)
The objective of this study was to investigate training profiles and motivation of male and female youth soccer players in different age groups and levels of play. A total of 1075 youth soccer players (U15-U19) from the Bavarian Football Association (BFV) in Germany completed a survey which investigated the total hours of training per week, and hours of training spent in endurance, sprint, technical/tactical, strength and other training and warm-up and cool-down procedures. Significant differences (p<0.05) between male high- and low-level players were seen in the amount of hours in sprint, technical/tactical and strength training. These differences were also found on motivation of the players. The total amount of training increased significantly with age in female players, but the only difference between high- and low-level players was in the amount of endurance training in the U19-group and game-related motivation in the U17-group. This study provides guidelines for training load and content in youth soccer players by gender, age and skill levels.